PENGUKURAN KUALITAS LAYANAN DALAM BIDANG PENDIDIKAN TINGGI - Ariesya Aprillia; Nonie Magdalena (Universitas Kristen Maranatha, 2018)
The service industry plays an important role in a nation's economy including higher education services. The performance of the quality of higher education services is determined by the quality of service delivery provided to the students. Quality of service in education is determined by the extent to which student needs and expectations can be met. How well students will later perceive the quality of their educational services will greatly contribute to the continuity of universities in the dynamics of long-term competition. The purpose of this study was to examine and analyze how the quality of service of Maranatha Christian University is viewed from the gap between the service experienced and the expected service. The service quality measurement instrument uses seven factors: contact personnel (faculty/ lecturer), reputation, physical evidence, contact personnel (administration), curriculum, responsiveness, and access to facilities. The technique used is simple random sampling with 418 respondents. Measurement instruments are tested using validity test, reliability test, and Importance and Performance Analysis (IPA). Based on the results of data processing using IPA five things that have not been matched as expected by the student when the five things are considered important by students. These are classroom arrangement, classroom comfort, immediate announcement notice, availability of parking space, and availability of access to nonclassroom learning. Keywords: IPA; Service Quality